ISSUES ON THE DEVELOPMENT OF TEACHER’S PEDAGOGICAL COMMUNICATION SKILLS (EDUCATION IN THE 21ST CENTURY, 2023)
Pedagogical communication requires from a teacher not only high professional skills, cognitive qualities, a wide horizon, social-cultural and psychological-pedagogical competences but also a mastery of a wide range of communication means, methods, ways and styles as well as an ability to apply them in a certain situation. In order to achieve the best results in pedagogical communication it is important to consider the possibilities of communication means and ways between teachers and students.Achievement of positive results in this process also depends on a teacher’s empathy and reflection, mastery of inspiration and persuasion methods as well as on the ability to take into account the interlocutor’s representative system, listen to and understand them and make an impact by the use of inspiration and persuasion methods. In this context there arises a necessity to master communication means, methods and a variety of ways according to a situation. A teacher’s ability to establish a rapport with students also plays an important role during communication. Building active, stable and effective relationships by mutual understanding promotes rapport and a social-psychological favourable atmosphere.Rapport is like a mirroring of the interlocutor not only by gestures, but also by the use of tone of speech, breathing, vocabulary, means of expression, intonation, emphasis and grammatical forms. Establishment of rapport is an essential component of communication, which requires emotional, sensory, reflexive, perceptive, linguistic, non-linguistic and paralinguistic abilities and means. All the means of expression need to be considered for encouraging rapport such as voice, tone of speech, mimics, gestures, state of mind, management of emotions, social-perceptive abilities such as attention, sensitivity, speech accent, its speed and rhythm.An important factor for building rapport is empathy, which is expressed through a teacher’s choice of necessary means of communication, culture of self-control, respect for a student’s person, tolerance and fairness from a pedagogical perspective. A modest, relaxed and natural composure and discretion are vital during communication; in contrast, a conceited and pathetic style hinders natural talks and exchange of information in a free communication atmosphere.Communication culture is a necessary component of a teacher’s professional competence, which is not only achieved through a mastery of theoretical knowledge about communication forms, means and ways but it is also acquired in the process of their continuous improvement in practice and reflection on one’s professional activity.
Keywords: Keywords: Communication, verbal and non-verbal communication means, rapport, reflection, empathy, mirroring, social-perceptive abilities, expression means of mimic and pantomime.